A comparison of production of embryogenic callus from three selected cocoa (theobroma cacao L.) clones - Goh, Suzanne (University Malaysia Sarawak (UNIMAS), 2013)
A research study was conducted to determine the best surface sterilization treatments and also to compare the production of embryogenic callus from three selected cocoa clones: MCB C5, MCB C8 and QH 1003 that were collected from MCB, Kota Samarahan. These cocoa clones were selected based on their superior quality compared to others. A total of 4 surface sterilization treatments tested and Treatment 2 which was immersion in 70% ethanol slowly agitated (1 minute) and immersion in 15% Clorox® (10 minutes) was found to be the best surface sterilization treatment. Comparison of production of embryogenic callus was done to assist the study of induction on somatic embryo production. Somatic embryogenesis is promoted for clonal propagation cocoa because it is able to produce somatic embryos that have identical characteristics with seed-derived plants. The Pennsylvania State University group protocol was used to induce somatic embryos from floral explants. Comparison of percentage of callusing staminode explants were presented and discussed. The percentage of callusing staminode explants were varied under 4 different surface sterilization treatments. Under the same surface sterilization treatment, MCB C5 was found to have the highest percentage of callusing staminode explants. The observations on different type of callus were reported.